Local job multipliers in the United States: Variation with local characteristics and with high-tech shocks - Timothy J. Bartik; Nathan Sotherland (W.E. Upjohn Institute for Employment Research, 2019)
This paper provides new estimates of local job multipliers, the ratio of total jobs generated to some initial number of jobs created from a demand shock. Multipliers greatly affect benefits versus costs of local job-creation policies. These new estimates rely on improved methodology and data. The methodology better captures dynamic effects of demand shocks, specifies the model so that demand shocks are more comparable, and is more general in the types of demand shocks that are considered. The data has more industry detail than that used in previous studies. The local job multipliers estimated tend to be about one-quarter lower than typically estimated local multipliers, closer to 1.5 than to 2.0. In addition, demand shocks to all industries matter, not just to tradable industries. Multipliers are similar across different types of geographic areas, with county multipliers being only one-quarter below commuting zone multipliers and state multipliers only one-quarter above commuting zone multipliers. Multipliers are not larger for larger commuting zones, but they increase in commuting zones that have lower initial employment to population ratios. Multipliers are higher for high-tech industries, particularly in commuting zones with a larger initial high-tech share. In such high-tech local economies, high-tech multipliers may be close to 3. While our high-tech multipliers are greater than for other industries, our estimated high-tech multipliers are less than in some prior studies.
Keywords: R11; R23; 330; Multipliers; agglomeration economies; congestion effects; high-technology industries